Prenatal Genetic Diagnosis in Three Fetuses With Left Heart Hypoplasia (LHH) From Three Unrelated Families - Luo, Sukun; Chen, Luyi; Wei, Weizhong; Tan, Li; Zhang, Meng; Duan, Zhengrong; Cao, Jiangxia; Zhou, Yan; Zhou, Aifen; He, Xuelian (Frontiers in Cardiovascular Medicine, 2021)
Background: Congenital heart defects (CHDs) are the most common birth defects, and left heart hypoplasia (LHH) is a severe form of CHD and responsible for more than 20% cardiac deaths during the first week of life, however, its genetic causes remain largely elusive. Methods: Three families with fetal LHH were recruited. Genomic DNA from amniotic fluid or peripheral blood, and trio whole exome sequencing (trio-WES) and copy number variation sequencing (CNV-seq) were performed. Results: All the three couples had no family history, and mid-gestation ultrasound revealed LHH and other variable cardiovascular defects in the fetuses. Trio-WES revealed de novo pathogenic variations in KMT2D (p.Gly3465Aspfs*37) (NM_003482) and WDFY3 (p.Ser117Xfs*) (NM_014991), and CNV-seq identified a deletion of 150 kb encompassing NOTCH1. KMT2D and NOTCH1 previously have been reported to be associated with CHDs, however, WDFY3 is reported for the first time to be possibly related to CHD in human. Conclusion: Our study suggested that genetic component is an important risk factor for the development of LHH, and next generation sequencing is a powerful tool for genetic diagnosis in fetuses with CHDs and genetic counseling, however, more studies and data are need to establish the correlation of fetal phenotypes and genotypes.